Soziologische Revue : Besprechungen neuer Literatur (Oldenbourg Wissenschaftsverlag, 1978)
Sociological Review offers a comprehensive critical overview of current German-language sociology literature (including related fields and methodology). It publishes omnibus reviews, double and single reviews, thematic essays, maps of specific areas in sociology, and a symposium to carefully and rapidly inform readers about new articles, research fields, and current areas of controversy.